21 Real talk – a novel evidence-based, video-based communication skills training resource. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Parry, R; Whittaker, B; Pino, M; Watson, S; Hamlyn, S; Faull, C
Abstract : Background: Much palliative care communication training draws on sparse evidence about practice. Yet training's effectiveness depends on the strength of its underpinning evidence. An empirical, observational science of language and social interaction – 'Conversation Analysis' holds great promise because: it is generating copious evidence on communication, and healthcare–communication specifically; shows role–played interactions differ from authentic ones in fundamentally important ways; recent quantitative evaluations of interventions based on conversation analytic findings have shown effectiveness. Within a research and training development programme, we designed novel training resources – 'Real Talk' incorporating research findings and clips from video-recorded hospice consultations. We designed Real Talk to complement rather than replace existing resources. We report a preliminary evaluation of Real Talk's strengths and weaknesses. Method: Mixed-methods, qualitative evaluation entailing observations, interviews, and participant-completed feedback questionnaires. Results: We collected data from 11 events, 10 trainers across England, and 150 trainees. Conclusions: Trainees and trainers alike appreciated the video clips and their authentic nature. Observations and reports indicated Real Talk was particularly effective for encouraging participants to both emotionally engage with the nature of palliative care, and actively engage in discussion and overall learning about communication practices. Trainers used the video clips more than they did the research findings components; with a similar pattern seen in most trainees' feedback. Our decision to design Real Talk for trainers to use without initial intensive training meant we could rapidly and widely distribute the resources and evaluate their use. However, this also meant heavy reliance on trainers' existing facilitation skills, and on their allocation of adequate time to familiarise themselves with the materials. We argue that this is also why the research findings-based components were not put to full use by trainers. We are revising Real Talk and its delivery on the basis of our evaluation.